2018
DOI: 10.3390/app8091518
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Lead Ions from Water by a Low-Cost Alginate-Melamine Hybrid Sorbent

Abstract: A low-cost alginate-melamine hybrid sorbent (named as Alg-Mel) was designed and synthesized for the removal of Pb2+ from water. The as-prepared Alg-Mel sorbent exhibited high affinity and selectivity to Pb2+. The selectivity coefficients of the Alg-Mel for Pb2+/Cd2+, Pb2+/Cu2+, Pb2+/Cr3+ and Pb2+/Co2+ were all over 7. It is found that the hybrid sorbent could uptake 95.4% of Pb2+ from Pb2+-containing solutions (0.48 mM), and the maximum adsorption capacity for Pb2+ reaches 1.39 mmol/g (287.7 mg/g), which is mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The maximum adsorption capacities of mp-CA/GO for Pb 2+ , Cu 2+ , and Cd 2+ are 368.2, 98.1 and 183.6 mg/g, respectively. These values are higher than most of the reported heavy metal ion adsorbents [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 57%
“…The maximum adsorption capacities of mp-CA/GO for Pb 2+ , Cu 2+ , and Cd 2+ are 368.2, 98.1 and 183.6 mg/g, respectively. These values are higher than most of the reported heavy metal ion adsorbents [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 57%
“…The 4-aminoantipyrine-GO adsorbent was compared in terms of adsorption capacity with some recently reported adsorbents. It clears that, in terms of adsorption capacity, the proposed sorbent compares favorably with other adsorbents and its adsorption capacity is high compared to other adsorbents (Table 4) [70][71][72][73][74][75][76][77][78][79][80][81][82].…”
Section: Comparison Of Adsorption Behaviour Based On Literature Datamentioning
confidence: 99%
“…There are six papers focused on the design and synthesis of new materials for environmental science applications in this issue, in which two papers reported the synthesis of new sorbents for removal of Pb 2+ . The first paper that contributed by Li et al [5], introduces the design and synthesis of a low-cost Pb 2+ sorbent by modifying biocompatible alginate (Alg) with chemically stable melamine (Mel). It was found that the conjugation of Mel with Alg could greatly improve the chemical and physical stability, and enhance the reuse ability of the synthesized Alg-Mel sorbent.…”
Section: New Materials For Environmental Sciencementioning
confidence: 99%